The Influence of English Trainer Competence on the English Language Proficiency of Trainees in Community Learning Centers Across Banyuwangi Regency - Alvianita Nur Wahyuni; Ach Rasyad; Edi Widianto (Universitas Negeri Padang, 2023)
This study aims to determine the influence of tutor competence on the English language proficiency of training participants. The researcher applied a quantitative correlational research design and used simple linear regression analysis. The population studied was all English language training participants in the Community Learning Center (CLC) of Banyuwangi Regency, with a total of 10 CLCs that provide English language training. The research was conducted over 5 months, from August to December 2021, with a sample size of 33 participants from 10 CLCs. Proportional random sampling technique was used to obtain the sample. Data was collected through the administration of a questionnaire as the primary method. The questionnaire was distributed to the 10 CLCs identified as the sample. The results showed that the tutor competence in teaching English has a score of 83.4%, indicating excellent competence, while the English language proficiency of the participants has a score of 65.4%, indicating moderate proficiency. The influence of tutor competence has a value of 0.405, which has a